Study of untreated hypertensive subjects by means of continuous intra-arterial blood pressure recordings. Issue 6 (June 1978) - Goldberg, A D; Raftery, E B; Cashman, P M; Stott, F D
Abstract : Continuous recording of intra-arterial blood pressure and electrocardiograms has been performed in 41 ambulant untreated essential hypertensive subjects for periods up to 48 hours. Statistical analysis of the results has revealed: (1) A group of patients who developed a persistent tachycardia during the day. This response was not observed in a control population free of overt cardiovascular disease. (2) Three different haemodynamic responses to day-time activities suggesting different mechanisms for the production of high blood pressures. No normal controls are available for these changes. (3) No differences in responses between patients defined as 'labile' and 'fixed' hypertensives.